Elevator supervisory and controller system (ESCS) - Sarwadi, Sahrul Izwan (2006)
Elevator supervisory and controller system is a system that implemented to monitoring all events for conventional elevator system. This project presents further development and strategies on elevator supervisory and controller system. The elevator system itself controlled using programmable logic controller and the supervisory and controller system developed using computer based visual basic programming software. The parallel communication port interface card was use to link between elevator system modeling structure and the personal computer.